PENERAPAN TEKNIK PENGHASIL PERTANYAAN DISERTAI MEDIA KOMIK DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 KOTO SALAK KABUPATEN DHARMASRAYA TAHUN PELAJARAN 2012/2013 - Agustin, Eka Putriana; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2013)
This research is motivated by the students comprehension of mathematical concepts of class VIII SMPN 1 Koto Salak Kabupaten Dharmasraya year of learning 2012/2013 are still low. This study aims to determine the students comprehension of mathematical concepts that apply Teknik Penghasil Pertanyaan with using comics media better than students comprehension of mathematical concepts that apply learning conventional in class VIII SMPN 1 Koto Salak Kabupaten Dharmasraya year of learning 2012/2013. Type of research is experiment with randomized control group only design. The population in research is class VIII students that registrated on 2012/2013 year learning. Sampling technique is random. The instrument that used in this research is comprehension of mathematical concepts test in essay. Hypothesis testing using the U Mann Whitney test with MINITAB helping. The result of hypothesis test significant in 0,0003 it means less than Â = 0,05. So that can be conclude that the students comprehension of mathematical concepts that apply Teknik Penghasil Pertanyaan with using comics media better than students comprehension of mathematical concepts that apply conventional learning in class VIII SMPN 1 Koto Salak Kabupaten Dharmasraya year of learning 2012/2013.